Human Resource Ambidexterity and Sustainable Performance: Mediating HR-Based Quality Assurance and Moderating External Environment - MHD Andy Rasyid; Pangeran Pangeran (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose - This study examines how human resource ambidexterity contributes to sustainable performance in private higher education institutions. Despite increasing environmental pressures, limited research has clarified the mechanism through which ambidexterity is transformed into sustainable performance, particularly through HR-based quality assurance systems and the role of the external environment. Design/methodology/approach – A quantitative explanatory approach was employed using data from 95 private universities under LLDIKTI Region I. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with bootstrapping procedures to test direct, mediating, and moderating relationships. Findings - The results indicate that human resource ambidexterity significantly influences HR-based quality assurance (β = 0.243; p = 0.013) and sustainable performance (β = 0.258; p = 0.018). HR-based quality assurance has a strong positive effect on sustainable performance (β = 0.370; p < 0.001) and partially mediates the relationship (β = 0.090; p = 0.043). The external environment negatively moderates the relationship (β = −0.215; p = 0.023), suggesting reduced effectiveness of ambidexterity under high environmental uncertainty. Originality/value - This study extends ambidexterity theory by integrating HR-based quality assurance as a key mediating mechanism and highlighting the contingent role of the external environment. The findings emphasize that sustainable performance in private higher education depends more on internal HR capability alignment than external pressures, providing practical insights for strengthening quality assurance systems.